Visible-light-induced photocatalytic oxidation of nitric oxide and sulfur dioxide: Discrete kinetics and mechanism. (15th May 2016) - Han, Yinghui; Zhang, Junjun; Zhao, Yi
Abstract: A new photocatalyst was prepared using doped titanium dioxide (TiO2 ) with active species for the removal of nitric oxide (NO) and sulfur dioxide (SO2 ) under visible light irradiation. Nitrogen (N-), zirconium (Zr-), and nickel (Ni-) tridoped TiO2 was found to possess higher photocatalytic activity than single Ni-doping, single Zr-doping, bimetallic doping or un-doping TiO2 . X-ray diffraction patterns and ultraviolet–visible spectra suggest that N-, Zr-, and Ni-tridoped TiO2 is a mixed-crystal structure that enhances absorption in the visible light region. Kinetic experiments on the removal of NO and SO2 by N-, Zr-, and Ni-tridoped TiO2 under visible light irradiation were carried out in a self-designed photocatalytic reactor respectively. The effects of various operation factors on the reaction rates were evaluated. The reaction rates were successfully expressed by Langmuir–Hinshelwood model. Based on ion chromatography analysis, a visible light induced photocatalytic removal mechanism has been proposed based on N-, Zr-, and Ni-tridoped mixed-crystal TiO2 . Graphical abstract: Highlights: N-, Zr-, Ni-tridoped TiO2 possesses higher visible-light photocatalytic activity. Removal kinetics of SO2 and NO obeyed the Langmuir–Hinshelwood model. Effects of flue gas concentrations and reaction temperature were considerable. IC analysis revealed photocatalytic removal mechanism.